Garapan Tari Gadis Rambang Serampu Jaye - Putri, Mufty Audya Cahyani (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The Serampu Jaye Princess Dance is a dance that originates from Rambang District, Muara Enim Regency, South Sumatra Province. The phenomenon of the Ptri Serampu Jaye dance talks about the history of the village which was adopted by the community and the village government, which is a dance that originates from Rambang District. The aim of this research is to describe the form of the Serampu Jaye Princess Dance in Rambang District, Muara Enim Regency. This dance creation includes aspects of movement exploration, story concept, accompanying music, costumes, and other stage elements. The results of the research obtained by the author are that the theme is related to the history of the village raised by the Rambang community, the storyline/dramatic plot is this plot with the fast and slow dance of the Princess Serampu Jaye there are 4 scenes of movement, a minimum of 3 dancers danced by young women, beautiful make-up, open stage: feature/free according to the event being held, shawl properties, the lighting used is yellow or bright lights symbolizing a soft and graceful dance while red lights indicate a tense atmosphere, and the setting used feature/free according to the stage during the Putri Serampu Jaye dance performance.